Answer:
Step-by-step explanation:
Given that A is a square matrix and A is idempotent
![A^2 = A](https://tex.z-dn.net/?f=A%5E2%20%3D%20A)
Consider I-A
i) ![(I-A)^2 = (I-A).(I-A)\\= I^2 -2A.I+A^2\\= I-2A+A\\=I-A](https://tex.z-dn.net/?f=%28I-A%29%5E2%20%3D%20%28I-A%29.%28I-A%29%5C%5C%3D%20I%5E2%20-2A.I%2BA%5E2%5C%5C%3D%20I-2A%2BA%5C%5C%3DI-A)
It follows that I-A is also idempotent
ii) Consider the matrix 2A-I
![(2A-I).(2A-I)=\\4A^2-4AI+I^2\\= 4A-4A+I\\=I](https://tex.z-dn.net/?f=%282A-I%29.%282A-I%29%3D%5C%5C4A%5E2-4AI%2BI%5E2%5C%5C%3D%204A-4A%2BI%5C%5C%3DI)
So it follows that 2A-I matrix is its own inverse.
Answer: 18x^3-9x^2+21x
Solution:
3x(6x^2-3x+7)=
Applying the distributive property in the multiplication to eliminate the parentheses:
(3x)(6x^2)+(3x)(-3x)+(3x)(7)=
(3*6)x^(1+2)+3*(-3)x^(1+1)+(3*7)x=
18x^3-9x^2+21x
Answer:
Q1. -45
Q2. -10
Q3. 31?
Step-by-step explanation:
Q1 -- you times -8 and 2 which comes out to -16. Since you have -16 + 1 inside of the parentheses you add 1 to -16 which comes out to -15. Then you take -15 times 3 and it comes out to -45.
Q2 -- the m gets replaced by the 5 so now its -2 times 5. Which comes out to -10. Then you take -10 times 2, which is -20. Now take -20 + 10 which gives us the answer of -10.
Q3 -- I'm not completely sure on this one but I think the equation would transfer to this 2*5 + 5*3 + 2*3. So 2*5 is 10, 5*3 is 15, and 2*3 is 6. Add them all together and you get 31.
I hope this was right and it helps you!
What is in the drop down menu????